Ketimpangan Sosial Pada Sumberdaya Pertanian di Desa Sawangan Kecamatan Tombulu Kabupaten Minahasa - Seba, Tri Putra Kurnia; Memah, Melsje Yellie; Benu, Noortje Marsellanie (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to analyze social inequality in agricultural resources in Sawangan Village, Tombulu District, Minahasa Regency. This study was conducted from April 2024 to June 2024. The research method used is a descriptive method to analyze the existing data. The data used are primary data and secondary data. Primary data was obtained directly from respondents by conducting direct interviews using a prepared questionnaire, while secondary data was obtained from other information data related to this study. The results of the study showed the results of a total score of 2631 which was obtained from the total score of inequality in land, inequality in capital and inequality in technology and information so that social inequality in agricultural resources in Sawangan Village, Tombulu District was in the high inequality criteria.